STEM-integrated project-based learning: Students’ critical thinking skills in trigonometry - Kristoforus Nofenaris Agung; Meiva Marthaulina Lestari Siahaan; Rika Handayani; Lailin Hijriani (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: This study was motivated by the importance of critical thinking skill in solving problem and making the decision. In addition, low level of students’ critical thinking skills issue in mathematics learning, particularly in trigonometry Aims: To address this issue, a STEM-integrated Project-Based Learning (PjBL-STEM) model was implemented. Method: This study employed a mixed-method approach combining quantitative and qualitative data. The sample consisted of 50 tenth-grade students at SMA Negeri Manufui, divided into an experimental class; 25 students and a control class; 25 students. Data were collected through a critical thinking skills test, student response questionnaires, and interviews. Results: The results of the independent samples t-test showed a significant difference between the experimental and control classes (Sig. = 0.001 < 0.05). The mean posttest score of the experimental class (52.83) was higher than that of the control class (45.33). The N-Gain analysis indicated a low improvement category in both classes; however, the experimental class (26.29%) showed a higher increase compared to the control class (4.50%). Student responses toward the PjBL-STEM implementation were highly positive, with more than 90% agreement. Qualitative findings revealed that project-based experiences helped students recall concepts, identify reasoning errors, and reflect on problem-solving processes. Conclusion: STEM-integrated PjBL model was effective in improving students’ critical thinking skills and fostering active, collaborative, and meaningful learning. Continuous implementation supported by structured guidance and critical thinking exercises is recommended to achieve more optimal learning outcomes.